2015
DOI: 10.13189/ujer.2015.031125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Communication Skills of Physical Education and Sport Students in Turkish Universities

Abstract: This study assessed the communication skills of the students studying in physical education and sports schools in various universities in Turkey. A total of 1854 Physical Education and Sports students in five Turkish universities participated in the study. The instrument used to gather information for this study comprised the demographic information of participants and Communication Skills Assessment Scale (CSAS) composed of 25 items. The 5 point likert-type scale was developed by Korkut in 1996 and did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
2
12
0
2
Order By: Relevance
“…Students' communication skills need to be improved through education in order to prepare students in the context of facing technological changes and rapidly developing social changes. Communication is the most important thing that humans need to adapt to the environment (Aydin, 2015). Communication skills can be defined as message transmission that involves a shared understanding between the contexts in which communication takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Students' communication skills need to be improved through education in order to prepare students in the context of facing technological changes and rapidly developing social changes. Communication is the most important thing that humans need to adapt to the environment (Aydin, 2015). Communication skills can be defined as message transmission that involves a shared understanding between the contexts in which communication takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Through Randai, students can be trained to communicate. Communication skills are communication skills that can be defined as transmitting messages that involve a shared understanding of the context in which communication takes place (Aydin, A. D., 2015;Khan, A., Khan, S., & Khan, M., 2017). Asemanyi, A.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study results were also in synch with those of several similar studies. For example, Aydin (2015) found that university students who participated in PE and sports in school displayed higher level of communication skills. Aykora, Tekin, Ozdag, Dereceli, & Uzunkaya (2010) also found that the PE students had higher communication skills than fine arts students.…”
Section: Discussionmentioning
confidence: 99%
“…Sports may be utilized to support communication and self-sustaining development for an entire affected community (Henley, Schweitzer, de Gara, & Vetter, 2007). A sports environment allows people to learn the skills that help in effective communication, and to use these skills in their social life (Aydin, 2015). Abakay (2013) stated that sports are an important factor in the development of communication skills.…”
Section: Introductionmentioning
confidence: 99%